2014
DOI: 10.1111/jsm.12696
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Intravaginal Ejaculatory Latency Time and National Institutes of Health-Chronic Prostatitis Symptom Index in the Four Types of Premature Ejaculation Syndromes: A Large Observational Study in China

Abstract: Introduction Besides lifelong premature ejaculation (LPE) and acquired premature ejaculation (APE), Waldinger and Schweitzer proposed two addition PE syndromes (variable PE [VPE] and subjective PE [SPE]). Aim We assessed the associations between intravaginal ejaculatory latency time (IELT) and National Institutes of Health-Chronic Prostatitis Symptom Index (NIH-CPSI) in men with different PE syndromes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 32 publications
1
18
0
1
Order By: Relevance
“… Trial flow diagram. *The E l‐ S akka et al., 2008 study (reference [31]) is included in both samples; references [38] and [39] refer to the same study. ED = erectile dysfunction, P E = premature ejaculation; IIEF = I nternational I ndex of E rectile F unction.…”
Section: Methodsmentioning
confidence: 99%
“… Trial flow diagram. *The E l‐ S akka et al., 2008 study (reference [31]) is included in both samples; references [38] and [39] refer to the same study. ED = erectile dysfunction, P E = premature ejaculation; IIEF = I nternational I ndex of E rectile F unction.…”
Section: Methodsmentioning
confidence: 99%
“…This syndrome includes urogenital pain, ejaculatory pain, urinary dysfunction, and sexual dysfunction. In the literature, CP has been closely linked with PE (42,117-120). While the co-existence of these conditions is common, a true causal relationship or mechanism has not been established.…”
Section: Urologic Risk Factorsmentioning
confidence: 99%
“…In this study, the PE cases included (confirmed and probable cases of PE) based on a Premature Ejaculation and Diagnostic Tool (PEDT) score of > 9 and proportion of premature ejaculation was found 26.4% (74 out of 280 men), which was consistent with previously reported majority of the study findings. [7][8][9][10][11][12] Due to the unavailability of published data on premature ejaculation in Bangladesh, results could not be compared in Bangladesh context. In Malaysia, studies have reported prevalence of PE of 29.0% and 49.1%.…”
Section: Discussionmentioning
confidence: 99%
“…On average, most studies reported a prevalence ranging from 20 % to 31.6%. [7][8][9][10][11][12] The Diagnostic and Statistical Manual of Mental Disorders (DSM), edition-IV (Text Revision) by the American Psychiatric Association (APA) defines PE as persistent or recurrent ejaculation with minimal sexual stimulation before, on, or shortly after penetration and before the person wishes it, with the disturbance causing marked distress or interpersonal difficulty and is not due exclusively to the direct effects of a substance (e.g., withdrawal from opioids). 6 PE is classified into four groups, namely, lifelong PE, acquired PE, natural variable PE and premature-like ejaculatory dysfunction.…”
Section: Introductionmentioning
confidence: 99%